2016
DOI: 10.1159/000448341
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Levels and Mortality in Hemodialysis Patients: A Retrospective Cohort Study

Abstract: Background: Hyperkalemia is common in patients receiving maintenance hemodialysis. However, few studies have examined the association between serum potassium level and mortality. Methods: This study used annual cohorts of hemodialysis patients during 2007-2010. To determine hyperkalemia prevalence, monthly hyperkalemia was defined as serum potassium level ≥5.5 mEq/l; prevalence was calculated as a ratio of hyperkalemia episodes to follow-up time, reported separately by long and short interdialytic interval. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 28 publications
1
100
0
1
Order By: Relevance
“…It is important to emphasize two factors that demonstrate the great vulnerability of patients without RRF during the LII. The first is related to the fact that the morbimortality associated with hyperkalemia in patients on HD is even more significant when potassium values are above 6 mEq/L, which occurred in 83% of patients without RRF in our study 24,25 . The second was the large variation of serum potassium levels in these patients throughout the LII, since, although starting from values similar to those of patients with RRF at the beginning of the interval, they reached significantly higher values at the end, which exposed them to a higher electrolyte gradient during HD session and increased the risk of adverse events 9 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is important to emphasize two factors that demonstrate the great vulnerability of patients without RRF during the LII. The first is related to the fact that the morbimortality associated with hyperkalemia in patients on HD is even more significant when potassium values are above 6 mEq/L, which occurred in 83% of patients without RRF in our study 24,25 . The second was the large variation of serum potassium levels in these patients throughout the LII, since, although starting from values similar to those of patients with RRF at the beginning of the interval, they reached significantly higher values at the end, which exposed them to a higher electrolyte gradient during HD session and increased the risk of adverse events 9 .…”
Section: Discussionmentioning
confidence: 72%
“…One of the possible explanations for this is that these data, unlike ours, were not obtained exclusively after the LII, when serum potassium levels are generally higher than in the middle of the week. In this regard, Yusuf et al 24 found a 2 to 2.4-fold higher prevalence of hyperkalemia after the LII when compared to the short interval, in a cohort of American dialysis patients between 2007 and 2010. However, in the data obtained from DOPPS (Dialysis Outcomes and Practice Patterns Study, which assessed data from 20 countries between 1996 and 2015), the difference between serum potassium levels obtained after the long and short interdialytic interval ranged from only 0.01 mEq/L in China to 0.19 mEq/L in Germany 25 .…”
Section: Discussionmentioning
confidence: 96%
“…Few previous studies have considered the impact of elevated serum K + level, with most of them focussing on the relationship between serum K + levels and adverse prognosis in patients with cardiovascular or chronic kidney diseases 8, 11, 12, 2123 . Among these studies, there were evidences showing the clinical significance of elevated serum K + levels, i.e., >4.7 mmol/L or >4.0 mmol/L, for worse patient prognosis 9, 10, 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This electrolyte imbalance is prevalent in patients with cardiovascular disease or impaired kidney function 3, 4 , and the recent use of several medications related to serum potassium (K + ) levels has further increased its incidence 57 . Moreover, hyperkalaemia is associated with worse prognosis and can induce critical arrhythmia 812 . Hence, management of this electrolyte imbalance has been suggested in clinical guidelines and is widely practised 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of two large dialysis data bases found that hyperkalemia (≥5.5 mEq/l) was found about 17 times per 100 patient‐months and was 2.0–2.4 times more likely after the long versus short interdialytic interval .…”
mentioning
confidence: 99%